The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1967
DOI: 10.1097/00132586-196710000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative and Operative Management of Patients With Phaeochromocytoma

Abstract: Before the introduction of adrenergic blocking agents and pressor substances operative removal of a phaeochromocytoma was a hazardous procedure, with a mortality of up to 25% (Graham, 1951). A mortality of 50% has been reported in operations on patients with unsuspected turnours (Apgar and Papper, 1951 ;Riddell, Schull, Frist, and Baker, 1963

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
45
0
1

Year Published

1970
1970
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 10 publications
0
45
0
1
Order By: Relevance
“…In early studies, life-threatening intraoperative catecholamine release has been quickly identified as the cause of increased blood pressure, various cardiac arrhythmias including ventricular tachycardia and fibrillation, left ventricular failures, myocardial ischemias, and strokes following induction of anesthesia or tumor manipulation (13,14). Prolonged postoperative hypotension followed the abrupt withdrawal of circulating catecholamines associated with tumor removal and accounted for most operative deaths (15).…”
Section: Historical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…In early studies, life-threatening intraoperative catecholamine release has been quickly identified as the cause of increased blood pressure, various cardiac arrhythmias including ventricular tachycardia and fibrillation, left ventricular failures, myocardial ischemias, and strokes following induction of anesthesia or tumor manipulation (13,14). Prolonged postoperative hypotension followed the abrupt withdrawal of circulating catecholamines associated with tumor removal and accounted for most operative deaths (15).…”
Section: Historical Backgroundmentioning
confidence: 99%
“…Prolonged postoperative hypotension followed the abrupt withdrawal of circulating catecholamines associated with tumor removal and accounted for most operative deaths (15). Pheochromocytoma removals were associated with a mortality rate of 20-45% in first reports (13,14). Prolonged high preoperative levels of circulating vasopressors released from pheochromocytomas were assumed to cause a vasoconstriction, leading to arterial hypertension and a chronic decrease in blood volume (13)(14)(15).…”
Section: Historical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…~,2,5 If vasopressors become necessary, most authors recommend the continuous infusion of L-norepinephrine (4 mg/500 ml). 1,8,5 This latter measure is only temporarily necessary in most cases, provided adequate fuid replacement has been achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Präoperativ ist eine Alpharezeptorblockade angezeigt, um perioperative kardiovaskuläre Komplikationen zu minimieren [5,7] Im Kapitel "Direkte orale Antikoagulanzien bei Adipositas" des Beitrags war der Abschnitt zur Dosisreduktion auf S. 41 in Bezug auf die eGFR teilweise nicht korrekt. Richtig muss es heißen: Die Nierenfunktion ist für die korrekte Anwendung der DOAK von größter Bedeutung und sollte regelmäßig während der Therapie kontrolliert werden.…”
unclassified